Prevalence in Athletes with Intellectual, Anthropometric, and Physical Disabilities-Conditional in Athletics - Antonio Jesus Perez Sierra; Alberto Bautista Sanchez Oms; Alberto Miguel Morales Fabregas; Manuel Octavio Encinas Trujillo; Ana Erika Gutierrez Valdez (Universitas Pendidikan Indonesia, 2022)
This study aimed to verify the prevalence of athletes with intellectual, anthropometric, and physical-conditional disabilities in Athletics. Mixed research was conducted employing descriptive, exploratory, and non-experimental studies. Document analysis, surveys, interviews, measurements, and statistical analysis were used. The reliability and validity of the instruments showed a confidence interval of (95%), with a standard value of (p0.05). This prevalence study involved ten male athletes with disabilities (age ±13.6, weight ±58.3, and height ±1,605). The results showed that physical-conditional anthropometric characteristic was the main variable distinguishing the athletes. Furthermore, based on the mean value of each indicator, it also relied on the upper and lower extremities and functional conditions. In conclusion, greater attention should be given, especially to athletes with certain physical conditions, to achieve better results in Olympics.